The Role Of Bank Indonesia In Stabilizing Indonesia's Economy Through Inflation Control: Peran Bank Indonesia Dalam Menstabilkan Perekonomian Indonesia Melalui Pengendalian Inflasi - Vindi Kusuma Wardani (International Journal of Economics, Business and Innovation Research, 2022)
Inflation is one of the classic problems in an economy which can result in a decrease in people's real income which on an ongoing basis has a negative impact on the macro economy. The increase in inflation is one of the indicators of economic stability which has become the center of attention for economic players. This research was conducted to know the Role of Bank Indonesia in Stabilizing the Indonesian Economy through Inflation Control. The research method used is a descriptive quantitative method, namely the technique of collecting and analyzing, and presenting quantitative data descriptively. This study uses a time series system, where data is collected based on data from the last 6 years, from 2017 to 2022. The data used is secondary data obtained from the Central Statistics Agency (BPS). The results obtained in the study are that the inflation rate from 2017 to 2022 has increased by 4.94 percent and decreased by 1.68 percent. The inflation rate from December 2021 to February 2022 was stable at around 2 percent. Based on the results obtained, the role of Bank Indonesia through monetary policy is needed in controlling inflation, namely by using a reference interest rate called the BI 7-Day Repo Rate (BI 7DRR). If inflation is rising, Bank Indonesia will raise the BI 7DRR, and if inflation is experiencing a deflation/decrease, Bank Indonesia will lower the BI 7DRR interest rate.